Análise entoacional e construcional das construções condicionais insubordinadas adversativas no português do Brasil - Alves, Camila Pires (Universidade Federal de São Carlos, 2022)
The phenomenon of "insubordination" (EVANS, 2007) is defined as the use of constructions that have some degree of subordination but are used independently without being subordinated to a main clause. Thus, the main objective of this work is to provide an intonational analysis from a constructional perspective (LANGACKER, 2008; TRAUGOTT; TROUSDALE, 2013) of conditional insubordinate constructions headed by "se" with adversative value in Brazilian Portuguese. Therefore, the adversative meaning of these constructions is understood as the result of the correlation of formal and functional properties, including the intonational aspect. Although Constructions Grammars defend the independence of linguistic levels, prosody is little considered both in research based on this approach and in studies of insubordinate constructions. In this dissertation, on the other hand, the intonation of these constructions is described, starting from an ad hoc corpora consisting of insubordinate adversative conditional constructions and conditional protases of the same lexical structure. The analyzes showed that the insubordinate adversative conditional constructions do not have a homogeneous intonation pattern. However, the identified intonation patterns indicate a prosodic function of prominence that proves the contrastive meaning of these constructions and distinguishes them from other types of insubordinate constructions (HIRATA-VALE, 2015; SILVESTRE, 2017). By comparing insubordinate adversative conditional constructions and subordinating conditional protases, it was proved that in these cases intonation acts as the only distinguishing feature between these two types of constructions. In a synchronic perspective, the insubordinate adversative conditional constructions were also subjected to a constructional description, according to the parameters of compositionality, productivity, and generality/schematicity (LANGACKER, 2008; TRAUGOTT; TROUSDALE, 2013), in order to understand the formal and functional specificities of these structures. For this purpose, a data corpus was created from two corpora, the Corpus do Português (Cdp), available online, and the C-Oral (RASO; MELLO, 2012), and the morphosyntactic and semantic-pragmatic description carried out by Alves and Hirata-Vale (2020, 2021) on these structures was also adopted. As a result, these constructions were less compositional, since the adversative meaning is mapped by the correlation of the subparts of these constructions; they are partially schematic, since they have a part that needs to be filled in and another part that is fixed; and finally, they are productive, through the expansion of their subschemata. The purpose of this study, then, is to show the contributions that arise from the inclusion of the prosodic level in studies of a cognitive-functional nature, and to introduce this type of analysis of conditional insubordinate constructions with adversative value in Brazilian Portuguese.
Intonational and constructional analysis of insubordinate adversative conditional constructions in Brazilian Portuguese
Keywords: Insubordinação; Condicionais insubordinadas; Entoação; Gramática de construções; Sincronia; Insubordination; Insubordinate conditionals; Intonation; Construction Grammar; Synchrony; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA